PEMANFAATAN TUMBUHAN OBAT OLEH SUKU MANGE DI KECAMATAN TALIABU UTARA KABUPATEN PULAU TALIABU PROVINSI MALUKU UTARA - Yusri La Usaha; Euis F.S. Pangemanan; Marthen T. Lasut (COCOS, 2017)
ABSTRACTTraditional medicine has long been known by our ancestors since time immemorial. The utilization of medicinal plants by Mange tribe especially those whose raw materials come from nature has long been known and this knowledge has been passed down from generation to generation. This research has been conducted in April - May and November 2016 with the aim to know the types and ways of utilizing medicinal plants. Data were collected through direct interviews of Batra (traditional healers) and field observations. The results showed that 40 species of plants from 29 families were used as medicine by boiling, given directly, taken without boiling and in the form of potion.Keywords: Traditional healers, medicinal plants, Mange tribe.